MOTIF DAN KEPUASAN KOMUNITAS ACID PADA MEDIA SOSIAL DISCORD SEBAGAI SARANA PEMENUHAN KEBUTUHAN INFORMASI - Maria Clara Irsa Setya Tumewu; Nani Kurniasari (Jurnal Pustaka Komunikasi, 2022)
Computer Mediated Communication encourages the formation of virtual communities in the new media era. The shift in communication patterns to become more effective and efficient is one of the advantages that can be felt through the presence of the Internet in the daily life of its users. Discord as the main medium for exchanging information for members of the Indonesian Autoclutch community, specifically discusses sim racing or virtual racing which is in great demand by various social, economic, and age groups. Thus, the existence of Discord as a means of fulfilling information needs that has been used by more than 100 million users every month is interesting to be studied further. This study aims to analyze Discord as a medium for meeting the information needs of the ACID community using Uses and Gratifications Theory. The methodology used in this study is based on the positivistic paradigm, through a quantitative approach, with an explanatory type, using measuring tools in the form of a questionnaire, simple correlation analysis data analysis techniques, and Discrepancy Theory to see a comparison between motives and satisfaction obtained. The results showed that there was a moderate level of satisfaction with a percentage of 82%.